2002
DOI: 10.1007/s00240-002-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

The early effects of partial outflow obstruction on contractile properties of diabetic and non-diabetic rat bladder

Abstract: The aim of this study is to determine the early effects of partial outflow obstruction (POO) on the detrusor contractility of diabetic (DM) and non-diabetic rats. A total of 67 adult female Wistar rats with average weight of 214+/-3.1 g were randomized into five groups as control ( n=6), sham operated ( n=6), obstructed ( n=18), DM ( n=19), and DM with obstruction ( n=18). Intraperitoneal injection of 60 mg/kg streptozotocin was performed to achieve DM. Partial bladder neck obstruction was created surgically b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…In the current study, we found that 8 weeks of diabetes caused increases in in vitro contractile responses to EFS, which is consistent with several previous studies [16,17] . EFS results in a release of several neurohumoral transmitters, which in turn stimulate postsynaptic receptors mediating contraction.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, we found that 8 weeks of diabetes caused increases in in vitro contractile responses to EFS, which is consistent with several previous studies [16,17] . EFS results in a release of several neurohumoral transmitters, which in turn stimulate postsynaptic receptors mediating contraction.…”
Section: Discussionsupporting
confidence: 82%
“…Other models of markedly enhanced diuresis such as sucrose feeding and Brattleboro rats often but not always mimicked findings with STZ injection. BOO as diuresis‐independent model of bladder hypertrophy always caused different changes of muscarinic responses as compared to STZ injection and the combination of both pathologies exhibited a complex response . A study comparing two diuresis‐independent models of bladder hypertrophy, that is, surgically‐induced denervation and BOO also found discordant alterations of muscarinic responses, giving further support to the hypothesis that changes in contractility are related to a specific model and not directly to the presence of bladder hypertrophy.…”
Section: Exploration Of Links Between Hypertrophy and Bladder Dysfuncmentioning
confidence: 68%
“…While one study from the Longhurst group reported a reduced EFS response in bladder base and dome, later studies from this group and others reported increased EFS responses in STZ‐treated rats. Other reports from the Longhurst group and others found no major change in EFS‐induced contraction.…”
Section: Exploration Of Links Between Hypertrophy and Bladder Dysfuncmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been suggested in recent studies that the purinergic system also contributes to bladder contractility, and it can become dominant under pathological conditions. In addition, neuronal and myogenic components consisting the detrusor contractility under pathological conditions have also become the topics of various studies [9,10] .…”
Section: Discussionmentioning
confidence: 99%